Low-carbon high-belite / high-iron phase mineral material as well as preparation method and application thereof
By preparing low-carbon high-Belite/high-speed iron phase mineral materials, the problem of poor crack resistance caused by high hydration and exothermic release of silicate cement is solved, and the reduction of cement hydration and exothermic release of heat and improving crack resistance is achieved. effect.
Patent Information
- Application Number
- CN202411874904.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-12-19
AI Technical Summary
The existing silicate cement has high hydration and heat release, resulting in poor crack resistance.
By preparing low-carbon high-Belite/high-iron phase mineral materials, using calcium, siliceous, aluminum and iron raw materials, combined with sintering additives, calcination conditions are regulated, and mineral materials containing high-Belite and iron phase are generated. Used as cement mix or concrete mix.
The hydration and heat exogenous amount of cement is reduced, crack resistance and chloride ion penetration are improved, and the stability and durability of cement are enhanced.
Smart Images

Figure CN119430716A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of building materials, and in particular relates to a low-carbon high-belite / high-iron phase mineral material and a preparation method and application thereof. Background Art
[0002] As an important building material, silicate cement is widely used in concrete structures. The main phase of silicate cement is C3S, with a content of about 50% to 70%. C3S has the characteristics of early strength and fast hardening, but its CaO content is high and the firing temperature is high, the corresponding carbon emissions and firing energy consumption are relatively high, and the early hydration heat release is high, which is easy to produce internal stress and cracking. Therefore, in the cement industry, new methods are needed to reduce carbon emissions and firing energy consumption, and reduce the risk of cement cracking.
[0003] In order to improve the anti-cracking and anti-corrosion performance of cement-based materials and enhance the stability of the structure, it is extremely important to control the hydration heat release and aluminum component content of the cementitious materials. At present, in basic theoretical research, actual production and application, the following methods are mainly used: adjusting the mineral composition of cement clinker, reducing the content of high-heat components such as C3S and C3A, and producing medium and low-heat silicate cement; using large amounts of fly ash, mineral powder and other mineral admixtures to reduce the amount of cement and reduce the occurrence of cracks.
[0004] However, this type of method has limited ability to reduce the heat release of cement, and it greatly affects the coagulation and hardening of cement-based materials, affecting the strength of cement-based materials. At the same time, the lower the aluminum content in cement, the lower its chloride ion solidification capacity will be, which is not conducive to the development of cement's resistance to chloride salt corrosion. Therefore, it is urgent to reduce the heat release of cement and enhance the anti-cracking and anti-corrosion properties of cement by preparing active mineral materials. Summary of the invention
[0005] The purpose of the present invention is to overcome the above technical deficiencies, provide a low-carbon high-belite / high-iron phase mineral material and its preparation method and application, and solve the technical problem in the prior art that silicate cement has high hydration exotherm resulting in poor anti-cracking and corrosion resistance.
[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In the first aspect, the present invention provides a low-carbon high-belite / high-iron phase mineral material. The raw materials include 90 to 110 parts of calcium raw materials, 0 to 26 parts of silicon raw materials, 2 to 29 parts of aluminum raw materials, 7 to 45 parts of iron raw materials, and 1 to 5 parts of sintering additives, calculated by mass.
[0007] In a second aspect, the present invention provides a method for preparing a low-carbon high-belite / high-iron phase mineral material, comprising the following steps: crushing and grinding a calcium raw material, a silicon raw material, an aluminum raw material and an iron raw material respectively, and mixing them with a sintering additive in proportion to obtain a raw material; the raw material is calcined, cooled, ground and sieved to obtain a low-carbon high-belite / high-iron phase mineral material.
[0008] In a third aspect, the present invention provides an application of a low-carbon high-belite / high-iron phase mineral material as a concrete admixture or cement admixture.
[0009] In a fourth aspect, the present invention provides a cement obtained by mixing cement clinker and a mixed material, wherein the mixed material is the above-mentioned low-carbon high-belite / high-iron phase mineral material; the mixed material accounts for 5 to 80% of the total mass of the cement.
[0010] In a fifth aspect, the present invention provides a concrete comprising cement, coarse aggregate, fine aggregate, admixture and water, wherein the admixture is the above-mentioned low-carbon high-belite / high-iron phase mineral material; the admixture accounts for 5 to 60% of the total mass of the admixture and cement.
[0011] Compared with the prior art, the beneficial effects of the present invention include: The present invention uses calcium raw materials, silicon raw materials, aluminum raw materials and iron raw materials as main raw materials, and adjusts the calcination system under the action of the firing additive to generate a low-carbon high-belite / high-iron phase mineral material. The mineral material has high content of belite and iron phase, and also contains part of α'-type dicalcium silicate with high gelling activity, which can be used as a cement admixture and cement clinker to grind cement or directly added to concrete as an admixture. When added to concrete, while maintaining the high compressive strength of concrete, the hydration heat release is reduced, the crack resistance is improved, and the resistance to chloride ion penetration is enhanced. Therefore, the low-carbon high-belite / high-iron phase mineral material of the present invention is added to cement to effectively improve the stability of low-heat and corrosion-resistant products, and is suitable for large-volume concrete engineering projects in marine environments; at the same time, the preparation method of the low-carbon high-belite / high-iron phase mineral material that enhances the crack resistance and corrosion resistance of cement of the present invention is simple, which is conducive to industrial production, and while reducing the environmental load, the sustainability and durability of the cement-based material structure are improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 is the lithofacies distribution of Example 2 of the present invention; wherein, 1: β -C2S; 2:C4AF; 3:C3A. DETAILED DESCRIPTION
[0013] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0014] At present, silicate cement has the defect of high hydration heat release, which leads to poor crack resistance and corrosion resistance. Simply adjusting the mineral composition of cement clinker can only reduce the heat release of cement to a limited extent, and will affect its mechanical properties, resulting in low strength. Therefore, the existing technology cannot reduce the heat release of cement and enhance the crack resistance and corrosion resistance of cement while ensuring strength. Based on this, the present invention is established.
[0015] In the first aspect, the present invention provides a low-carbon high-belite / high-iron phase mineral material. The raw materials include 90 to 110 parts of calcium raw materials, 0 to 26 parts of silicon raw materials, 2 to 29 parts of aluminum raw materials, 7 to 45 parts of iron raw materials, and 1 to 5 parts of sintering additives, calculated by mass.
[0016] Preferably, calculated as oxides, the CaO content in the calcium raw material is above 45%, the SiO2 content in the silicon raw material is above 80%, the Al2O3 content in the aluminum raw material is above 20%, and the Fe2O3 content in the iron raw material is above 30%.
[0017] Preferably, the calcium raw materials include limestone, carbide slag, and steel slag; the silicon raw materials include high-silicon sandstone and coal gangue; the aluminum raw materials include secondary aluminum ash and red mud; and the iron raw materials include iron tailings, copper slag, and steel slag. Preferably, limestone is used as the calcium raw material for the raw materials of mineral materials; high-silicon sandstone is used as the silicon raw material with its extremely high silicon content, without the need to add additional correction raw materials, and its intermolecular contact is close, the particles are fine, and the effect on grindability is small, which is conducive to firing; secondary aluminum ash is a by-product of the aluminum industry, and as an aluminum raw material, it promotes the resource utilization of solid waste in the building materials industry; iron tailings are metallurgical industry waste slag, which can be used as an iron raw material in the raw materials of mineral materials.
[0018] Preferably, the firing additive includes a mineral containing one or more elements of boron, phosphorus, magnesium and fluorine.
[0019] Further preferably, the boron-containing mineral comprises borax.
[0020] Preferably, the High Score software is used to perform Rietveld refinement on the XRD measurement data of the low-carbon high-belite / high-iron phase mineral material formed by calcination to obtain the phase mass composition, which includes: tricalcium silicate (C3S) 0-6%, dicalcium silicate 25%-79%, tricalcium aluminate (C3A) 0-2%, and iron phase (one or more of C4AF, C6AF2 or C6A2F) 18%-75%.
[0021] Further preferably, the dicalcium silicate comprisesβ Type dicalcium silicate and α 'type dicalcium silicate; the mineral composition of low carbon high belite / high iron phase mineral materials includes: tricalcium silicate (C3S) 0-1.8%, β Type dicalcium silicate ( β -C2S) 23.5%~69.8%, α ' type dicalcium silicate ( α '-C2S) 5.1%~9.1%, tricalcium aluminate (C3A) 0~1.5%, iron phase (one or more of C4AF, C6AF2 or C6A2F) 18.6%~66.8%.
[0022] In a second aspect, the present invention provides a method for preparing a low-carbon high-belite / high-iron phase mineral material, comprising the following steps: The calcium raw material, silicon raw material, aluminum raw material and iron raw material are crushed and ground respectively, and then mixed with the sintering additives in proportion to obtain raw materials; The raw material is calcined, cooled, ground and sieved to obtain a low-carbon high-belite / high-iron phase mineral material.
[0023] Preferably, the crushing is crushing into particles with a particle size of ≤5 mm; and the grinding is grinding into a powder particle size of ≤75 μm.
[0024] Preferably, the calcination temperature is 1200° C. to 1350° C., and the calcination time is 30 to 120 min.
[0025] Preferably, cooling is air cooling to room temperature.
[0026] In a third aspect, the present invention provides an application of a low-carbon high-belite / high-iron phase mineral material as a concrete admixture or cement admixture.
[0027] In a fourth aspect, the present invention provides a cement obtained by mixing cement clinker and an admixture, wherein the admixture is the above-mentioned low-carbon high-belite / high-iron phase mineral material; the admixture accounts for 5 to 80% of the total mass of the cement (i.e., the total mass of the admixture and cement clinker).
[0028] The low-carbon high-belite / high-iron phase mineral material obtained by the invention can be used as a cement admixture and ground together with cement clinker to produce cement.
[0029] Preferably, the cement clinker includes one or more of silicate cement clinker, ferroaluminate cement clinker and sulphoaluminate cement clinker.
[0030] Preferably, the cement clinker includes one or more of medium-heat cement clinker and low-heat cement clinker.
[0031] In a fifth aspect, the present invention provides a concrete comprising cement, coarse aggregate, fine aggregate, admixture and water, wherein the admixture is the above-mentioned low-carbon high-belite / high-iron phase mineral material; the admixture accounts for 5 to 60% of the total mass of the admixture and cement.
[0032] Preferably, high belite / high iron phase mineral materials with different aluminum-iron ratios prepared within the above range can be mixed with each other in any proportion as a composite active admixture to effectively improve the crack resistance and corrosion resistance of the system.
[0033] The mechanism of action and advantages of the present invention: (1) The principle that the low-carbon high-belite / high-iron phase mineral material of the present invention can enhance the anti-cracking and anti-corrosion performance of cement is based on the composition and reaction process of the mineral phase in cement clinker. The present invention uses limestone, high-silicon sandstone, secondary aluminum ash, and iron tailings as raw materials, and boron-containing mineral borax as a firing additive, and calcines to generate high-belite / high-iron phase mineral materials. The mineral material has high content of belite and iron phase; wherein the belite / iron phase refers to a specific mineral phase in the clinker, mainly including β -C2S and iron phase (one of C4AF, C6AF2 and C6A2F), and also contains some α'-type dicalcium silicate with high gelling activity. Because of the extremely low C3S content, these mineral phases not only have low synthesis temperatures, but also can effectively reduce the heat release of cement-based materials when added to cement as admixtures. Moreover, they continue to react in the middle and late hydration process, and can still form a large amount of hydration products in the middle and late hydration process, such as hydrated calcium silicate (CSH) gel and hydrated calcium aluminate. These gels have high gelling and crystallization activities and can form a dense hydration product structure. And the calcium alumina ferrite with different activities designed by reasonable matching can continuously solidify chloride ions, effectively enhancing the anti-cracking and anti-corrosion properties of cement.
[0034] (2) The low-carbon high-belite / high-iron phase mineral material of the present invention has excellent burnability, and the calcination temperature is 1200 ℃ ~ 1350 ℃. The lower decomposition and calcination temperature makes it have significant energy-saving and emission reduction effects compared with traditional cement clinker, and reduces the coal consumption and carbon emissions of clinker during the production process, has less impact on the environment, and also reduces the production cost of clinker, which is economical and affordable.
[0035] (3) The low-carbon high-belite / high-iron phase mineral material of the present invention gives full play to the synergistic effect of belite and iron phase minerals. In the middle and late hydration process, the belite strength growth rate is high, and its hydration heat is low, the water resistance is good, the iron phase strength continues to increase in the late stage, and the chloride salt resistance is good. After matching the design of the two mineral compositions and reasonably controlling the aluminum / iron ratio and dosage in the iron phase minerals, it is directly added to the existing bulk silicate cement as an active admixture, which not only greatly reduces the heat release of cement hydration and reduces the cracking of silicate cement, but also can control the aluminum dissolution rate according to the difference in reaction activity during the cement hydration process, thereby improving the mechanical properties and corrosion resistance of cement.
[0036] In summary, the present invention solves the defects of high carbon emissions and poor anti-permeability of current silicate cement products from the source, and provides a low-carbon high-belite / high-iron phase mineral material that enhances the anti-cracking and anti-corrosion performance of cement; the low-carbon high-belite / high-iron phase mineral material of the present invention can be used as a cement admixture or as a concrete admixture. When added to concrete, while maintaining high compressive strength of concrete, it reduces hydration heat release, improves anti-cracking performance, and enhances resistance to chloride ion penetration, expands the engineering application performance of high-belite / high-iron phase cement mineral materials, and extends the service life of engineering structures.
[0037] The present invention is further described in detail below with reference to specific embodiments. The limestone, high-silicon sandstone, secondary aluminum ash, and iron tailings used are crushed into particles with a particle size of ≤5 mm, and then ground into powder with a particle size of ≤75 μm by a ball mill. The chemical composition of the raw materials is shown in Table 1.
[0038] Table 1 Chemical composition of each raw material (%)
[0039] Example 1 (1) According to the mineral design composition of the mineral material, 110 parts of limestone, 25 parts of high-silicon sandstone, 5 parts of secondary aluminum ash, 11 parts of iron tailings and 3 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 80% of dicalcium silicate (C2S) and 20% of iron phase (C4AF); (2) calcining the raw material at 1300 °C for 120 min and then rapidly cooling it to room temperature by wind power; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0040] Example 2 (1) According to the mineral design composition of the mineral material, 106 parts of limestone, 20 parts of high-silicon sandstone, 8 parts of secondary aluminum ash, 17 parts of iron tailings and 3 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 70% of dicalcium silicate (C2S) and 30% of iron phase (C4AF); (2) calcining the raw material at 1300 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0041] Example 3 (1) According to the mineral design composition of the mineral material, 102 parts of limestone, 15 parts of high-silicon sandstone, 11 parts of secondary aluminum ash, 22 parts of iron tailings and 2 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 60% of dicalcium silicate (C2S) and 40% of iron phase (C4AF); (2) calcining the raw material at 1300 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0042] Example 4 (1) According to the mineral design composition of the mineral material, 98 parts of limestone, 10 parts of high-silicon sandstone, 14 parts of secondary aluminum ash, 28 parts of iron tailings and 2 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 50% dicalcium silicate (C2S) and 50% iron phase (C4AF); (2) calcining the raw material at 1240 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0043] Example 5 (1) According to the mineral design composition of the mineral material, 94 parts of limestone, 4 parts of high-silicon sandstone, 17 parts of secondary aluminum ash, 34 parts of iron tailings and 1 part of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 40% dicalcium silicate (C2S) and 60% iron phase (C4AF); (2) calcining the raw material at 1240 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0044] Example 6 (1) According to the mineral design composition of the mineral material, 92 parts of limestone, 1 part of high-silicon sandstone, 19 parts of secondary aluminum ash, 37 parts of iron tailings and 1 part of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 3% of tricalcium silicate (C3S), 30% of dicalcium silicate (C2S), 1% of tricalcium aluminate (C3A), and 66% of iron phase (C4AF); (2) calcining the raw material at 1240 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0045] Example 7 (1) According to the mineral design composition of the mineral material, 109 parts of limestone, 25 parts of high-silicon sandstone, 2 parts of secondary aluminum ash, 14 parts of iron tailings and 3 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 80% of dicalcium silicate (C2S) and 20% of iron phase (C6AF2); (2) calcining the raw material at 1240 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0046] Example 8 (1) According to the mineral design composition of the mineral material, 105 parts of limestone, 19 parts of high-silicon sandstone, 4 parts of secondary aluminum ash, 22 parts of iron tailings and 3 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 70% dicalcium silicate (C2S) and 30% iron phase (C6AF2); (2) calcining the raw material at 1240 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0047] Example 9 (1) According to the mineral design composition of the mineral material, 101 parts of limestone, 13 parts of high-silicon sandstone, 5 parts of secondary aluminum ash, 29 parts of iron tailings and 2 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 60% of dicalcium silicate (C2S) and 40% of iron phase (C6AF2); (2) calcining the raw material at 1240 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0048] Example 10 (1) According to the mineral design composition of the mineral material, 97 parts of limestone, 8 parts of high-silicon sandstone, 7 parts of secondary aluminum ash, 37 parts of iron tailings and 2 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 50% dicalcium silicate (C2S) and 50% iron phase (C6AF2); (2) calcining the raw material at 1200 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0049] Embodiment 11 (1) According to the mineral design composition of the mineral material, 92 parts of limestone, 2 parts of high-silicon sandstone, 9 parts of secondary aluminum ash, 44 parts of iron tailings and 1 part of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 40% dicalcium silicate (C2S) and 60% iron phase (C6AF2); (2) calcining the raw material at 1200 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0050] Example 12 (1) According to the mineral design composition of the mineral material, 92 parts of limestone, 10 parts of secondary aluminum ash, 45 parts of iron tailings and 1 part of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 3% tricalcium silicate (C3S), 34% dicalcium silicate (C2S), 1% tricalcium aluminate (C3A), and 62% iron phase (C6AF2); (2) calcining the raw material at 1200 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0051] Embodiment 13 (1) According to the mineral design composition of the mineral material, 110 parts of limestone, 26 parts of high-silicon sandstone, 8 parts of secondary aluminum ash, 7 parts of iron tailings and 3 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 80% of dicalcium silicate (C2S) and 20% of iron phase (C6A2F); (2) calcining the raw material at 1350 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0052] Embodiment 14 (1) According to the mineral design composition of the mineral material, 107 parts of limestone, 21 parts of high-silicon sandstone, 12 parts of secondary aluminum ash, 11 parts of iron tailings and 3 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 70% dicalcium silicate (C2S) and 30% iron phase (C6A2F); (2) calcining the raw material at 1350 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0053] Embodiment 15 (1) According to the mineral design composition of the mineral material, 103 parts of limestone, 17 parts of high-silicon sandstone, 16 parts of secondary aluminum ash, 15 parts of iron tailings and 2 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 60% of dicalcium silicate (C2S) and 40% of iron phase (C6A2F); (2) calcining the raw material at 1350 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0054] Example 16 (1) According to the mineral design composition of the mineral material, 99 parts of limestone, 12 parts of high-silicon sandstone, 21 parts of secondary aluminum ash, 19 parts of iron tailings and 2 parts of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 50% dicalcium silicate (C2S) and 50% iron phase (C6A2F); (2) calcining the raw material at 1270 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0055] Embodiment 17 (1) According to the mineral design composition of the mineral material, 96 parts of limestone, 7 parts of high-silicon sandstone, 25 parts of secondary aluminum ash, 23 parts of iron tailings and 1 part of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 40% dicalcium silicate (C2S) and 60% iron phase (C6A2F); (2) calcining the raw material at 1270 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0056] Embodiment 18 (1) According to the designed mineral composition of the mineral material, 92 parts of limestone, 2 parts of high-silicon sandstone, 29 parts of secondary aluminum ash, 27 parts of iron tailings and 1 part of borax are mixed into a uniform raw material; the mineral mass composition of the designed mineral material includes: 30% of dicalcium silicate (C2S) and 70% of iron phase (C6A2F).
[0057] (2) calcining the raw material at 1270 °C for 120 min and then quenching; (3) After grinding and screening, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0058] In order to highlight the changes in the final mineral composition of the mineral material, a comparative test was set up by co-changing the raw materials and calcination temperature. The mineral composition of the designed mineral material was designed with reference to the mineral composition of general Portland cement clinker.
[0059] Comparative Example 1 (1) According to the mineral composition of the mineral material, 123 parts of limestone, 22 parts of high-silicon sandstone, 7 parts of secondary aluminum ash, and 5 parts of iron tailings are mixed into a uniform raw material. The mineral mass composition of the designed mineral material includes: tricalcium silicate (C3S) 62%, dicalcium silicate (C2S) 20%, tricalcium aluminate (C3A) 8%, and iron phase (C4AF) 10%; (2) calcining the raw material at 1430 °C for 120 min and then quenching; (3) After grinding, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0060] Comparative Example 2 (1) According to the mineral composition of the mineral material, 123 parts of limestone, 22 parts of high-silicon sandstone, 5 parts of secondary aluminum ash, and 7 parts of iron tailings are mixed into a uniform raw material. The mineral mass composition of the designed mineral material includes: tricalcium silicate (C3S) 62%, dicalcium silicate (C2S) 20%, tricalcium aluminate (C3A) 8%, and iron phase (C6AF2) 10%; (2) calcining the raw material at 1400 °C for 120 min and then quenching; (3) After grinding, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0061] Comparative Example 3 (1) According to the mineral composition of the mineral material, 123 parts of limestone, 22 parts of high-silicon sandstone, 8 parts of secondary aluminum ash, and 4 parts of iron tailings are mixed into a uniform raw material. The mineral mass composition of the designed mineral material includes: tricalcium silicate (C3S) 62%, dicalcium silicate (C2S) 20%, tricalcium aluminate (C3A) 8%, and iron phase (C6A2F) 10%.
[0062] (2) calcining the raw material at 1450 °C for 120 min and then quenching; (3) After grinding, the average particle size of the clinker mineral is 15 μm, and a low-carbon high-belite / high-iron phase mineral material is obtained to enhance the anti-cracking and anti-corrosion properties of cement.
[0063] Performance Testing 1. The XRD measurement data of the low-carbon high-belite / high-iron phase mineral material formed by calcination were subjected to Rietveld refinement using High Score software to obtain the phase mass composition; and the designed composition of the low-carbon high-belite / high-iron phase mineral material for enhancing the anti-cracking and anti-corrosion properties of cement obtained in the above embodiments and comparative examples and the Rietveld refinement results were statistically analyzed, and the results are shown in Table 2 below.
[0064] Table 2 Design composition of low carbon high belite / high iron phase mineral materials and Rietveld refinement results (%)
[0065] As shown in Table 2, the mineral composition of the low-carbon high-belite / high-iron phase mineral material obtained by the present invention includes: tricalcium silicate (C3S) 0-1.8%, β Type dicalcium silicate ( β -C2S) 23.5%~69.8%, α ' type dicalcium silicate ( α '-C2S) 5.1% to 9.1%, tricalcium aluminate (C3A) 0 to 1.5%, iron phase (one or more of C4AF, C6AF2 or C6A2F) 18.6% to 66.8%. In Comparative Examples 1-3, tricalcium silicate is the main mineral component.
[0066] 2. The petrographic analysis of the low-carbon high-belite / high-iron phase mineral material obtained in Example 4 was performed. The results are as follows: Figure 1 As shown, it can be seen that it generates more β -C2S (1) and C4AF (2), with a small amount of C3A (3).
[0067] 3. The performance test was conducted on the low-carbon high-belite / high-iron phase mineral materials obtained in the above embodiments and comparative examples to enhance the anti-cracking and anti-corrosion performance of cement as admixtures to prepare C45 concrete. The mix design is shown in Table 3, wherein the control group is a test without admixtures of mineral materials; the low-carbon high-belite / high-iron phase mineral materials obtained in the embodiments and comparative examples were used as admixtures to replace 20% of the cement mass fraction. P·I 42.5 cement was selected as cement. Medium sand with a fineness modulus of 2.8 was selected as sand. Clean crushed stone with two grades of 5-10 mm and 10-31.5 mm was selected, with good particle shape, hard texture and small linear expansion coefficient. An appropriate amount of polycarboxylic acid-based high-performance water reducer was selected to adjust the workability to be consistent, with a solid content of 30% and a water reduction rate of 30%. Tap water was selected as water.
[0068] Table 3C45 concrete mix design (kg / m 3 )
[0069] The prepared C45 concrete was cured to 28 d and 56 d, and then performance tests were carried out. The compressive strength and adiabatic temperature rise tests were carried out according to GB / T 50080-2016, and the chloride ion permeability coefficient was carried out according to GB / T 50082-2009. The results are shown in Table 4.
[0070] Table 4 Concrete performance test results of mineral materials obtained in various embodiments and comparative examples
[0071] It can be seen from Table 4 that, compared with the control group, the use of the low-carbon high-belite / high-iron phase mineral material of the present invention as an admixture can significantly improve the strength after 28 days, and the 28-day adiabatic temperature rise and chloride ion permeability coefficient are significantly lower than those of the control group.
[0072] Compared with the control group, the iron phase components in the admixtures were transformed into C4AF, C6AF2, and C6A2F by adjusting the component ratio and calcination temperature. As admixtures, they can stabilize or improve the compressive strength of concrete materials, but the 28-day adiabatic temperature rise and chloride ion permeability coefficient did not decrease, and the crack resistance and corrosion resistance were poor.
[0073] Compared with the comparative example, the low-carbon high-belite / high-iron phase mineral material is used as the admixture. Although the C3S and C3A contents are extremely low, the strength after 28 days is significantly improved, and the 28-day adiabatic temperature rise and chloride ion permeability coefficient are significantly lower than those of the comparative example, and the crack resistance and corrosion resistance are excellent.
[0074] Compared with Examples 1-6, the iron content in the admixture gradually increases, the C2S content gradually decreases, the adiabatic temperature rise has a slight improvement, the strength after 28 days and later is slightly reduced, but the chloride ion penetration resistance is improved. The same can be said for Examples 7-12 and Examples 13-18.
[0075] Compared with Examples 1-6, Examples 7-12 and Examples 13-18, the aluminum content in the admixtures with the same mineral component ratio increased and the iron content decreased, which slightly improved the compressive strength, but weakened the adiabatic temperature rise suppression and resistance to chloride ion penetration.
[0076] The low-carbon high-belite / high-iron phase mineral material for enhancing the crack and corrosion resistance of cement of the present invention is used as a concrete admixture by regulating the belite / iron phase content and the iron phase aluminum and iron content within a suitable range, so as to effectively improve the crack and corrosion resistance of concrete, and improve the crack resistance (28-day adiabatic temperature rise of 38.5-49.2°C) while ensuring high strength (28-day compressive strength of 53.5-62.8 MPa, 56-day compressive strength of 59.0-65.1 MPa), and at the same time enhance the chloride ion penetration resistance (28-day chloride ion penetration coefficient of 1.32×10 -12 m 2 / s~2.90×10 -12 m 2 / s). The high crack resistance of the present invention is due to the increase in the C2S content of the low exothermic mineral in the system; the high corrosion resistance is due to the generation of iron phases with different aluminum-iron ratios, which regulates Al to enter the hydration product during the hydration process to form C-(A,F)-H, thereby improving the adsorption of chloride ions by the system; the engineering application performance of high-belite / high-iron phase cement mineral materials is expanded, and the service life of engineering structures is extended.
[0077] Therefore, the present invention provides a low-carbon high-belite / high-iron phase mineral material for enhancing the anti-cracking and anti-corrosion properties of cement. The mineral material can be directly added to concrete as an admixture. It has low hydration exotherm, high mid- and late-stage strength, and low chloride ion permeability coefficient. It is added to cement to improve the stability of low-heat and corrosion-resistant products, and is suitable for large-volume concrete engineering projects in marine environments. At the same time, the preparation method of the low-carbon high-belite / high-iron phase mineral material for enhancing the anti-cracking and corrosion properties of cement of the present invention has a low synthesis temperature, which is conducive to industrial production.
[0078] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A low-carbon high-belite / high-iron phase mineral material, characterized in that: Calculated by weight, the raw materials include 90 to 110 parts of calcium raw materials, 0 to 26 parts of silicon raw materials, 2 to 29 parts of aluminum raw materials, 7 to 45 parts of iron raw materials, and 1 to 5 parts of sintering additives.
2. The low-carbon high-belite / high-iron phase mineral material according to claim 1, characterized in that: Calculated in terms of oxides, the CaO content in the calcium raw material is above 45%, the SiO2 content in the silicon raw material is above 80%, the Al2O3 content in the aluminum raw material is above 20%, and the Fe2O3 content in the iron raw material is above 30%.
3. The low-carbon high-belite / high-iron phase mineral material according to claim 1, characterized in that: The calcium raw materials include one or more of limestone, carbide slag and steel slag, the silicon raw materials include one or more of sandstone and coal gangue, the aluminum raw materials include one or more of secondary aluminum ash and red mud, and the iron raw materials include one or more of iron tailings, copper slag and steel slag.
4. The low-carbon high-belite / high-iron phase mineral material according to claim 1, characterized in that: The physical phase composition of the low-carbon high-belite / high-iron phase mineral material includes: 0-6% tricalcium silicate, 25%-79% dicalcium silicate, 0-2% tricalcium aluminate, and 18%-75% iron phase.
5. The low-carbon high-belite / high-iron phase mineral material according to claim 1, characterized in that: The firing additive includes a mineral containing one or more elements of boron, phosphorus, magnesium and fluorine.
6. The method for preparing the low-carbon high-belite / high-iron phase mineral material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The calcium raw material, silicon raw material, aluminum raw material and iron raw material are crushed and ground respectively, and then mixed with the sintering additives in proportion to obtain raw materials; The raw material is calcined, cooled, ground and sieved to obtain a low-carbon high-belite / high-iron phase mineral material.
7. The method for preparing the low-carbon high-belite / high-iron phase mineral material according to claim 6, characterized in that: Crushing is crushing into particles with a particle size of ≤5 mm; grinding is grinding to a powder particle size of ≤75 μm; The calcination treatment is performed at a temperature of 1200°C to 1350°C and for a time of 30 to 120 minutes.
8. Use of the low-carbon high-belite / high-iron phase mineral material as claimed in any one of claims 1 to 5 as a concrete admixture or cement admixture.
9. A cement, characterized in that: The cement clinker is prepared by mixing cement clinker and a mixed material, wherein the mixed material is the low-carbon high-belite / high-iron phase mineral material as described in any one of claims 1 to 5; the mixed material accounts for 5 to 80% of the total mass of the cement.
10. A concrete, characterized in that: The raw materials include cement, coarse aggregate, fine aggregate, admixture and water, wherein the admixture is the low-carbon high-belite / high-iron phase mineral material according to any one of claims 1 to 5; the admixture accounts for 5 to 60% of the total mass of the admixture and the cement.
Citation Information
Patent Citations
Low-carbon low-heat high-belite cement clinker based on waste concrete and preparation method of low-carbon low-heat high-belite cement clinker
CN114477810A
Solid waste-based low-carbon high-iron phase-belite system concrete and synergistic solid waste carbon sequestration method thereof
CN115340307A
Belite cement clinker, preparation method thereof and Belite Portland cement
CN118754471A
Solid-waste-based iron-rich high-belite sulphoaluminate cement clinker and preparation method thereof
CN118834027A
Ternesite - belite - calcium sulfoaluminate brick and method for producing same
EP2559674A1